If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + e = 13 Solving 10 + e = 13 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + e = 13 + -10 Combine like terms: 10 + -10 = 0 0 + e = 13 + -10 e = 13 + -10 Combine like terms: 13 + -10 = 3 e = 3 Simplifying e = 3
| -5-4a+5a=7 | | -8(b-3)=-24+4b | | c+10=12 | | 2x/3-58-2x | | .5x+6=x-4 | | 82+9x-6+6x-1=180 | | 25-5x=-13-8x | | 0=t^2-4t+6 | | 4x+4x+k=0 | | 2-8n=-8(n-2)+2n | | 2m+3=4m+13 | | 2x+9=-47-6x | | b-13=4 | | 20-6x=12-7x | | 2m+4=m+7 | | 6x-1+6x-6+82=180 | | 6x^2=34x-40 | | 20x^2-16x=4x | | 4w/7=56 | | -39=-22+d | | 4a^2+b^2+12a-4b+13=0 | | 6x^2-23=-21 | | 4+7x=-32+x | | 35=7/3w | | -36+8b=4(3+4b) | | a+23=25 | | (5x)+7=-2x | | 2c-10+6= | | -58x-2+6=8x-230.6 | | 262.818/28.26 | | x(2x-2)+x(2x-4)=(4x+7)(x-3) | | (2x^4+7x^3-8)-(7x^2-5x+4)= |